(3CfXeI GdJcGdja dCZQGV bjGS JcdaI GdEfJGL hGdNOeGJ (B/s - (3eQYj, YHO GdMj YHO GdMjs; (3eHGQc, UdGM GdOjf YHO GdefYe s; (3eUWai, eMehO eQGO s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI ddfTQ(B, s, 2002)
(3aj WHjYI GdUfGYI hYfGUQ JcdaI GdEfJGL(B-(3aj feGPL CfXeI JcGdja GdOGNd(B-(3aj feGPL CfXeI JcGdaj aj Xd eSehMGJ hNSGFQ GdJTZjd(B-(3bjGS JcdaI GdYedjGJ(B-(3bjGS JcdaI GdefJLGJ GdeJUdI hGdaQYjI YbhO GdebGhdGJ WhjdI GdCLd(B-(3bjGS GdJcdaI aj GdhMOGJ GdNOejI(B-(3fXGe GdEfJGL GdahQj hbjGS GdJcdaI ef NdGd GdJOab GdbjGSjs
Keywords: (3GdEfJGL(B- (3GdJcGdjas; (3GdJcGdjas